Factors to be considered when establishing the place of effective management in a digital economy - Augustin, Natalie (Department of Finance and Tax, 2016)
South Africa applies a residence-based tax system and accordingly a legal person or company is regarded as tax resident in South Africa if it is incorporated, established or formed in South Africa or if it has its place of effective management (POEM) in South Africa. Further, the POEM test is also used as the 'tie-breaker' rule in double taxation agreements (DTA's), which are based on the Organisation for Economic Co-operation and Development Model Tax Convention on Income and Capital and the Commentary thereto (OECD, OECD MTC, and OECD Commentary). The concept 'POEM' has never been defined for tax purposes, not in a South African context, neither internationally. Thus, when ascribing a meaning thereto, one is left to consider the South African Revenue Service's (SARS) interpretation and the OECD's interpretation thereof. Currently SARS considers the POEM to be located where policy and strategic decisions are executed and implemented by a company's senior management. On the other hand, the OECD considers the POEM to be where key management and commercial decisions of an entity's business as a whole are in substance made (it appears SARS is also leaning towards this interpretation, based on the most recent draft interpretation note released).